Differences among cigarette-only smokers compared to dual users of cigarettes and little cigars/cigarillos in the criminal justice population. (March 2019) - Schiavon, Samantha; Hodgin, Kathleen; Sellers, Aaron; Hendricks, Peter S.; Gaggar, Amit; Scarinci, Isabel; Cropsey, Karen L.
Abstract: Introduction: The FDA has restrictions on cigarettes; however, little cigars and cigarillos (LCCs) remain largely absent from these regulations. Due to their low prices and flavoring, many engage in dual use of both LCCs and cigarettes. Dual use is particularly prevalent among low income racial/ethnic minority groups. The purpose of this study was to (U.S. Department of Health and Human Services, 2014) conduct an exploratory examination among cigarette users compared to dual users on smoking characteristics; and (Centers for Disease Control and Prevention, 2016) to examine racial differences (White and Black) among cigarette users compared to dual users. Methods: Participants ( N = 500) were recruited from community corrections (i.e., parole/probation) and categorized as either cigarette-only (66.4%) or dual users (33.6%) if they used little cigars or cigarillos over a one-year period during a smoking cessation clinical trial. Results: Dual users were more likely to be younger, Black, males with lower educational attainment compared to cigarette-only smokers. Smokers with increased nicotine dependence were 17% more likely to be cigarette-only smokers compared to dual users. Racial differences revealed that White/cigarette-only smokers were more likely to report non-menthol use and higher cigarette consumption at the end of treatment compared to Black/cigarette-only or Black/dual users. Conclusions: This study contributes to our understanding of dual use among a disenfranchised group of smokers. Overall, dual users were more likely to be younger, Black, and male with lower reported nicotine dependence compared to cigarette-only users. Racial differences revealed that non-menthol smokers as well as smokers with greater cigarettes smoked at the end of treatment were more likely White/cigarette-only smokers. Highlights: Examined cigarette only users compared to dual users on smoking characteristics. Examined racial differences among cigarette users compared to dual users. Dual users were more likely to be young, Black, males with lower education. Dual users were more likely to reported lower nicotine dependence. Contributes to our understanding of dual use among disenfranchised smokers.